Cultural Understanding of the Students for Multicultural Education in the University - Sukardi, Joko Sri; Hanum, Farida; Dwiningrum, Siti Irene Astuti; Efianingrum, Ariefa (KnE Social Sciences, 2019)
This research maps the profile of students’ cultural understanding in Yogyakarta State University (UNY). The sample were the students from seven faculties at UNY. The quantitative data was analyzed using T-Test. The results show that there was a difference in cultural understanding among the students from all faculties. The background of the student does affect the understanding of multiculturalism. In general, the profile of students’ cultural understanding is good, but it needs to be upgraded as a capital for further development of multicultural education. Keywords: cultural understanding; multicultural education.